2022
DOI: 10.3389/fgene.2022.846101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics and Pathogenesis of the Floating Harbor Syndrome: Case Report of Long-Term Growth Hormone Treatment and a Literature Review

Abstract: Introduction: Floating Harbor syndrome (FHS) is an extremely rare disorder, with slightly more than a hundred cases reported worldwide. FHS is caused by heterozygous mutations in the SRCAP gene; however, little is known about the pathogenesis of FHS or the effectiveness of its treatment.Methods: Whole-exome sequencing (WES) was performed for the definitive molecular diagnosis of the disease. Identified variants were validated using Sanger sequencing. In addition, systematic literature and public data on geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Studies indicate that the syndrome may be caused by a defect in the downstream signaling pathway of IGF-1, as opposed to decreased secretion and/or activity of growth hormone or IGF-1. 8 Furthermore, studies have indicated that decreased growth hormone secretion or activity typically does not result in prenatal fetal growth restriction, whereas decreased IGF-1 secretion or activity is associated with prenatal fetal growth restriction or microcephaly. 1 In our case, the child has a growth hormone deficiency along with the normal range of birth length and weight, which is consistent with the study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the syndrome may be caused by a defect in the downstream signaling pathway of IGF-1, as opposed to decreased secretion and/or activity of growth hormone or IGF-1. 8 Furthermore, studies have indicated that decreased growth hormone secretion or activity typically does not result in prenatal fetal growth restriction, whereas decreased IGF-1 secretion or activity is associated with prenatal fetal growth restriction or microcephaly. 1 In our case, the child has a growth hormone deficiency along with the normal range of birth length and weight, which is consistent with the study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our observations are in good concordance with several gene-level studies. One example is the SRCAP gene linked to Floating-Harbor syndrome (FHS, OMIM 136140), in which causal variants have been identified only in 33rd and 34th exons [28]. At the same time, pathogenic variants outside of this hotspot region have been described in association with developmental delay, hypotonia, musculoskeletal defects, and behavioral abnormalities (DEHMBA, OMIM 619595) [29].…”
Section: Discussionmentioning
confidence: 99%
“…In male probands with delayed growth and bone age, intellectual impairment, skeletal and facial features, and partial responses to hormone treatment, we identified a c.7466C>G (p.Ser2489*) heterozygous pathogenic mutation in the last exon of the SRCAP (Snf2 related CREBBP activator protein) gene, thus suggesting a new model of floating harbor syndrome (FHS) pathogenesis. These genetic mutations have dominant-negative effects that explain the limited efficacy of growth hormone treatment in FHS [ 53 ].…”
Section: Human Monogenic Diseases: Population Genetics Researchmentioning
confidence: 99%